ANALISIS KUALITAS PELAYANAN, SARANA PRASARANA DAN LINGKUNGAN TERHADAP KEPUASAN PASIEN - Ulandari, Sripina; Yudawati, Sunarsih (Universitas Tribhuwana Tunggadewi, 2019)
The puskesmas must still be able to maintain the quality of services supported by adequate facilities and infrastructure and be supported by the creation of a clean, beautiful, neat and pleasant environment so as to meet the expectations or needs of patients. The purpose of this study was to analyze the relationship between the quality of services, facilities and the environment for patient satisfaction at Pujon Health Center Malang Regency.The type of research used is explanatory reset. The sampling technique used was purposive sampling. The sample in this study were patients who came to treatment (at least 2 times treatment) or patients who had used services to the Health Center as many as 150 respondents. Collecting data uses observation techniques, interviews, questionnaires and documentation. The data analysis used is multiple linear regression. Based on the results of the study prove the existence of a significant influence between the quality of service, infrastructure and environment on patient satisfaction in Health Center (p-value 0.034